ADDITIVE AND COMBINED GLAUCOMA THERAPY: PRINCIPLES AND PRACTICE - A. V. Kuroyedov; Z. M. Nagornova; Z. U. Tibieva; E. A. Krinitsyna; V. M. Sergeeva (Российский офтальмологический журнал, 2018)
The review summarizes the results of modern clinical practice of glaucoma treatment, in which diverse combinations of drugs are used. The search for new combinations of treatment of glaucoma patients is directed to the individual characteristics of the disease, but at the same time it should follow a uniform pattern of prescription sequence. Lifelong monitoring of glaucoma patients and prescriptions of medication are faced with a gradual decrease in drug effectiveness. Attention should be given to a falling tolerance to drugs, or reduced reaction to habitual administration of drugs and addiction, which requires increasing doses to achieve the expected effect of the drug. Clinical and organizational aspects of the situation are considered. For citation: Kuroyedov A.V., Nagornova Z.M., Tibieva Z.U., Krinitsyna E.A., Sergeeva V.M. Additive and combined glaucoma therapy: principles and practice. Russian ophthalmological journal. 2018; 11 (2): 71-81. doi: 10.21516/2072-0076-2018-11-2-71-81 (In Russian).